The feasibility of using pulsed-vacuum in stimulating calcium-alginate hydrogel balls - Jinnoros, J.; Innawong, B.; Udomkun, Patchimaporn; Parakulsuksatid, P.; Silva, J.L. (MDPI, 2021)
The effect of the pulsed-vacuum stimulation (PVS) on the external gelation process of calcium-alginate (Ca-Alg) hydrogel balls was studied. The process was conducted at four different working pressures (8, 35, 61, and 101 kPa) for three pulsed-vacuum cycles (one cycle consisted of three repetitions of 10 min of depressurization and 10 min of vacuum liberation). The diffusion coefficients (D) of calcium cations (Ca2+) gradually reduced over time and were significantly pronounced (p < 0.05) at the first three hours of the external gelation process. The rate of weight reduction (WR) and rate of volume shrinkage (Sv) varied directly according to the D value of Ca2+. A significant linear relationship between WR and Sv was observed for all working pressures (R2 > 0.91). An application of a pulsed vacuum at 8 kPa led to the highest weight reduction and shrinkage of Ca-Alg hydrogel samples compared to other working pressures, while 61 kPa seemed to be the best condition. Although all textural characteristics (hardness, breaking deformation, Young’s modulus, and rupture strength) did not directly variate by the level of working pressures, they were likely correlated with the levels of WR and Sv. Scanning electron micrographs (SEM) supported that the working pressure affected the characteristics of Ca-Alg hydrogel structure. Samples stimulated at a working pressure of 8 kPa showed higher deformation with heterogenous structure, large cavities, and looser layer when compared with those at 61 kPa. These results indicate the PVS is a promising technology that can be effectively applied in the external gelation process of Ca-Alg gel.